Animal Model of Severe Fever With Thrombocytopenia Syndrome Virus Infection - Sun, Jiawen; Min, Yuan-Qin; Li, Yunjie; Sun, Xiulian; Deng, Fei; Wang, Hualin; Ning, Yun-Jia (Frontiers in Microbiology, 2022)
Severe fever with thrombocytopenia syndrome (SFTS), an emerging life-threatening infectious disease caused by SFTS bunyavirus (SFTSV; genus Bandavirus, family Phenuiviridae, order Bunyavirales), has been a significant medical problem. Currently, there are no licensed vaccines or specific therapeutic agents available and the viral pathogenesis remains largely unclear. Developing appropriate animal models capable of recapitulating SFTSV infection in humans is crucial for both the study of the viral pathogenic processes and the development of treatment and prevention strategies. Here, we review the current progress in animal models for SFTSV infection by summarizing susceptibility of various potential animal models to SFTSV challenge and the clinical manifestations and histopathological changes in these models. Together with exemplification of studies on SFTSV molecular mechanisms, vaccine candidates, and antiviral drugs, in which animal infection models are utilized, the strengths and limitations of the existing SFTSV animal models and some important directions for future research are also discussed. Further exploration and optimization of SFTSV animal models and the corresponding experimental methods will be undoubtedly valuable for elucidating the viral infection and pathogenesis and evaluating vaccines and antiviral therapies.